2017
DOI: 10.23937/2378-3419/1410084
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Partial Orchiectomy in Treating Small Testicular Tumors in the United States

Abstract: Introduction and objectives: There is increasing evidence supporting the feasibility of Partial Orchiectomy (PO) as a treatment for small testicular tumors. However, the prevalence of this practice is still unknown. We used the Surveillance, Epidemiology, and End Results (SEER) registry to characterize national practice patterns for surgical management of patients with testicular tumors ≤ 2 cm in size, and we examined factors that determined performing PO in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Studies have reported that 60–70% of nonpalpable masses of less than 2 cm are nonmalignant lesions such as small benign Leydig or Sertoli cell tumors 2 , 3 , 16 18 . No difference was demonstrated in the cancer-specific survival between the RO and TSS groups in 5365 patients with tumors of less than or equal to 2 cm from the Surveillance, Epidemiology, and End Results database 18 , 19 . A report of the German Testicular Cancer Study Group included 73 patients receiving TSS, with a median follow-up of 91 months.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have reported that 60–70% of nonpalpable masses of less than 2 cm are nonmalignant lesions such as small benign Leydig or Sertoli cell tumors 2 , 3 , 16 18 . No difference was demonstrated in the cancer-specific survival between the RO and TSS groups in 5365 patients with tumors of less than or equal to 2 cm from the Surveillance, Epidemiology, and End Results database 18 , 19 . A report of the German Testicular Cancer Study Group included 73 patients receiving TSS, with a median follow-up of 91 months.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, secondgeneration AR antagonists cannot completely cure patients with CRPC and ultimately the disease progresses to lethal neuroendocrine prostate cancer (NEPC). The incidence of NEPC has significantly increased with the clinical use of AR inhibitors [34][35][36]. For this reason, we hypothesized that a new type of AR inhibitor, other than AR antagonists, could serve as a unique therapeutic agent for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Alanee et al, performed a large scale review of primary testicular cancer treatment between 1995-2011; and found that of 5,365 patients identified as having small testicular tumours that would be amenable to PO, only 2% had TSS performed (42). No difference was demonstrated in cancer specific survival between the RO and PO groups in the 5,365 patients with tumours ≤2 cm (42).…”
Section: Utilisationmentioning
confidence: 99%
“…Alanee et al, performed a large scale review of primary testicular cancer treatment between 1995-2011; and found that of 5,365 patients identified as having small testicular tumours that would be amenable to PO, only 2% had TSS performed (42). No difference was demonstrated in cancer specific survival between the RO and PO groups in the 5,365 patients with tumours ≤2 cm (42). Low utilisation of PO was also demonstrated in 81 patients with tumours <10 mm in size by Scandura et al, with only 5% undergoing PO rather than RO despite 69% of these cases being identified as benign at histopathology (35).…”
Section: Utilisationmentioning
confidence: 99%